Role of nano-hydrogels coated exosomes in bone tissue repair - Pan, Yuqi; Li, Yige; Dong, Wenjun; Jiang, Bowei; Yu, Yuhao; Chen, Yunsu (Frontiers in Bioengineering and Biotechnology, 2023)
As the development of nano-material, it is widely applied in different areas. Some nano-materials are designed to be biocompatible and can be used in medical field, playing an important role in disease treatment. Exosomes are the nanoscale vesicle with a diameter of 30-200 nm. Studies have shown that exosome have the effect of angiogenesis, tissue (skin, tendon, cartilage, et al.) repair and reconstruction. Nano-hydrogels are hydrogels with a diameter of 200 nm or less and can be used as the carrier to transport the exosome into the body. Some bone defect, bone infection or other complex bone disease are hard to deal with. The emerge of exosome coated nano-hydrogels may bring a new idea to solve these problems, improving the prognosis of patients. This review summarizes the function of nano-hydrogel coated exosome from different origins in bone tissue repair, intending to illustrate the potential use and application of exosomes coated nano-hydrogel in complex bone disease.